PYOTR BITSILLI IN THE PHILOSOPHICAL “CONVERSATION” OF RUSSIA ABROAD - D. V. RATUSHINA (Высшее образование в России, 2018)
The key theme of the paper is the heritage and ideas of Pyotr Mikhailovich Bitsilli (1879–1953) – historian, philosopher, literary critic. His style of thinking, special historical method of penetrating into investigated reality have not lost their relevance until today. Bitsilli was an active participant of philosophical “conversation”. It was a literary dispute on the nature of “national” and the destiny of Russian culture between Russian emigration thinkers. The paper is an attempt to make a reconstruction of this “conversation” from the position of an existential choice. Special attention is paid to the periodicals of the Russian émigré as a space for intellectual communication, as a means of retention of cultural heritage. Pyotr Bitsilli was a gifted polemicist, he had a talent to penetrate into the deeps of subjects and author’s conception. The paper dwells on Bitsilli’s reviews in the journal “Sovremennye zapiski” (Contemporary Notes).